Synthesis of lactic acid from glucose catalyzed by MOFs - Longfei Yan; Lijuan Su; Yu Zhang; Qihui Zhang; Bin Wu; Fuweng Zhang; Weiping Deng (Applied Catalysis O: Open)
Lactic acid is the monomer for the synthesis of polylactic acid (PLA), a biodegradable plastic. In industry, lactic acid is mainly produced through the fermentation of glucose, but the space-time yield of this process is relatively low. Therefore, the catalytic conversion of glucose to lactic acid has garnered significant attention as an alternative approach. In this study, Metal-Organic Frameworks (MOFs) were employed to catalyze the conversion of glucose in methanol to synthesize methyl lactate. The bonding modes of Al3+ with different ligands in Al-MOF result in variations in the ratios of Lewis acid to Brønsted acid, influencing the catalytic performance of Al-MOF. Among them, MIL-120, formed through the complete coordination of Al3+ with the four carboxyl groups of pyromellitic acid, exhibits the most suitable ratio of Lewis acid to Brønsted acid. Using MIL-120 as a catalyst, glucose was completely converted, achieving a methyl lactate yield of 43 % in methanol at 463 K and 1 MPa N2 for 2 h.